Examining the effects of changing physiological and psychological conditions and Schumann frequency on time perception and anticipation timing in male referees with EEG - Lale Yildiz Cakir; Ali Gurel Goksel; Gonul Babayigit Irez; Utku Sari; Aygun Akgul; Kaan Salman (Journal of Men's Health)
Background: Physical exertion and external stimuli can impact cognitive performance. This study explored how match-like environments and Schumann’s binaural beat stimulation affect time perception and anticipation timing, critical for football referees’ decision-making. Methods: Using a quasi-experimental time series design, 24 active male referees participated voluntarily. Time perception and anticipation timing were assessed under four conditions: baseline (B), aerobic exercise (E), aerobic exercise with 85 dB crowd noise (ECN) and 7.83 Hz Schumann binaural beat stimulation (SBS). Heart rate and electroencephalogram (EEG) data were continuously monitored. Data on time perception (ms), anticipation timing (ms), heart rate (bpm), and EEG (microvolts) were analyzed using repeated measures analysis of variance (ANOVA) in SPSS 26.0. Results: The results showed significant differences in time perception between E, SBS, ECN and SBS conditions (p < 0.05), but no significant differences in anticipation timing across conditions. EEG data revealed increased alpha and theta band power during the SBS condition compared to others (p < 0.05). Additionally, theta band power was significantly higher in the ECN condition than in the B condition (p < 0.05). The findings highlighted improved time perception under the ECN condition, with a positive correlation between elevated theta band power and enhanced time perception. However, despite a similar increase in theta power during the SBS condition, referees did not show significant improvements in time perception. Conclusions: These results suggest that theta oscillations may play a role in time perception, but other neurophysiological and environmental factors likely influence this relationship. Further research is needed to understand the complex interplay between these variables and their impact on cognitive performance in referees.